Infrared and conductivity studies on blends of PMMA/PEO based polymer electrolytes - Osman, Z.; Ansor, N.M.; Chew, K.W.; Kamarulzaman, N. (2005)
Poly(methylmetacrylate)/poly(ethylene oxide) (PMMA/PEO) based polymer electrolytes were synthesized using the solution cast technique. Four systems of PMMA/PEO blends based polymer electrolytes films were investigated: (1) PMMA/PEO system, (2) PMMA/PEO + ethylene carbonate (EC) system, (3) PMMA/PEO + lithium hexafluorophosphate (LiPF6) system and (4) PMMA/PEO + EC + LiPF6 system. The polymer electrolytes films were characterized by Impedance Spectroscopy and Fourier Transform Infrared Spectroscopy (FTIR). The FTIR spectra show the cornplexation occurring between the polymers, plasticizer and lithium salt. The FTIR results give further insight in the conductivity enhancement of PMMA/PEO blends based polymer electrolytes.